ALTERED CORTICOSTRIATAL CONNECTIVITY IN GAMBLING DISORDER - Bellmunt Gil, Albert (My University, 2022)
Gambling Disorder (GD) is officially recognized as a form of addiction, specifically, a behavioral addiction. It is characterized by manifesting maladaptive, compulsive gambling behavior, accompanied with craving, withdrawal and impaired control over behavior. It presents a prevalence of 1-2% in the adult population of the western society. GD is currently the only behavioral addiction present in the DSM-5, despite the fact that other compulsive disorders such as binge eating or compulsive buying are not yet officially admitted as addiction disorders. Addiction studies suggest a disturbance in the corticostriatal connectivity being one of the neural correlates affecting the reward and inhibitory system. Moreover, connections from the striatum to the frontal lobe have been demonstrated to participate in the formation of aberrant habits, characteristic of any form of addiction known to date. The aim of this thesis work was to study frontostriatal connectivity in GD. In this thesis work, GD was studied using resting-state functional magnetic resonance imaging (rs-fMRI). 13 individuals with diagnosed GD and 15 healthy controls (HC) underwent the scanning procedure. CONN Toolbox was used to do the preprocessing and the voxel-wise analyses for the neuroimaging data. The results show that when comparing GD with HC there is a significantly higher connectivity in the GD group between the right accumbens and the right dorsolateral prefrontal cortex (DLPFC). No correlation was found with the connectivity values and behavioral measures related with gambling. The results demonstrate that the frontostriatal circuit belonging to the reward system from the right accumbens to the right DLPFC is altered in the GD group.